Strategies to Utilize the Home Environment through the Implementation of Sustainable Development Goals (SDGs): Strategi Memanfaatkan Lingkungan Rumah Melalui Implementasi Sustainable Development Goals (SDGs) - Jariono, Gatot; Nurhidayat, N; Sudarmanto, Eko; Yunita, Prita; Nugroho, Haris; Maslikah, Uzizatun (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Empowering the use of the home environment as an Implementation of Sustainable Development Goals (SDGs) for the Wonosari Village Community, Gondangrejo District is an alternative in the form of a solution that is the basis for the method of implementing community service used in this activity. This community service is Assistance in the Empowerment of Education, Economy, and Socio-Culture as the Implementation of Sustainable Development Goals (SDGs) for the People of Wonosari Village, Gondangrejo District. This mentoring program involves the Wonosari Village Community, Gondangrejo District. This assistance is based on Sustainable Development Goals (SDGs) in the use of the home environment, there are various stages in the mentoring process, including providing assistance, organizing open classes, and reflection. The results of assistance in the use of the home environment, namely (a) plant cultivation by aquaponics with indicators of community achievement can follow and understand plant cultivation activities by aquaponics; (b) plant cultivation by hydroponics with indicators of community achievement can follow and understand plant cultivation activities by hydroponics; (c) cultivation of plants by cuttings with indicators of achievement of children can follow and understand plant cultivation activities by cuttings; (d) Plant cultivation by grafting with achievement indicators Children can follow and understand plant cultivation activities by grafting.